PROFESSIONAL DEVELOPMENT OF ENGLISH TEACHERS IN RSBI SCHOOLS IN SINGARAJA - Monik Rismadewi, Ni Wayan (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2012)
ABSTRACT Key Words : professional development, pedagogical competency, personal competency, social competency, professional competency. This research aims at describing the efforts that had already been done by English teachers in SD Negeri 3 Banjar Jawa and SMP Negeri 1 Singaraja on their professional development in terms of pedagogical, personal, social and professional competency, and the problems encountered in pursuing those competencies. The research was conducted by using descriptive qualitative design. The instruments used in this study were questionnaires, interview guide, obseravtional notes, and portfolio. The primary data were analyzed descriptively. Accordingly, the results of the study showed that: 1) Self-directed Development, Case-based Professional Development, and Cooperative-Collegeal Development were the types/models of the professional development that had been done by English teachers on their professional development, 2) Each of the professional developments was derived from some kinds of activities/efforts which had already been done by English teachers; 3) Time limitation, the lack of literatures, the lack and inequal opportunity to participate in scientific forum, the use of technology for self-development were several problems encountered by English teachers in pursuing their pedagogical, social and professional competency. Finally, from the result of the analysis it can be concluded that: 1) The efforts that had already been done by English teachers on their professional development in terms of pedagogical competency are: using various teaching media, using various teaching techniques and models, reading books, articles and journals about english and education, participating in scientific forums, using learning and teaching facilities, conducting assessment/evaluataion, conducting discussion with peers, conducting lesson study, 2) The efforts that had already been done by English teachers on their professional development in terms of personal competency are: Accepting and giving constructive critics and suggestions from peers, being discipline, and following religious activities in school, 3) The efforts that had already been done by English teachers on their professional development in terms of social competency are: participating in scientific forums, participating in professional community and organization, conducting discussion with peers. 4) The efforts that had already been done by English teachers on their professional development in terms of professional competency are: reading books, articles and journals about english, conducting research, using information and technology for self-development, 5) The problems encountered by English teachers in pursuing those four main competencys are: Problem in the context of Pedagogical competency: 1) Time limitation and lack understanding of how to conduct research especially in classroom action-based research, 2) The lack of literatures, and 3) Time limitation in conducting team teaching. Problem in the context of Social competency: The lack and inequal opportunity to participate in scientific forum. Problem in the context of Professional development: 1) The lack of literatures, and 2) The use of technology for self-development.